Comparison of Efficacy of Anti-interleukin-17 in the Treatment of Psoriasis Between Caucasians and Asians: A Systematic Review and Meta-Analysis - Zhang, Danyi; Qiu, Jianing; Liao, Xing; Xiao, Yi; Shen, Minxue; Deng, Yaxiong; Jing, Danrong (Frontiers in Medicine, 2022)
Background: Interleukin-17 (IL-17) monoclonal antibody drugs have been increasingly significant in the treatment of psoriasis, but it is not clear whether the efficacy is equivalent across ethnicities. Objectives: We sought to explore the differences of short-term efficacy of IL-17 inhibitors between Caucasians and Asians. Methods: The pooled log risk ratio (logRR) between groups was estimated. A meta-regression analysis on the logRR was performed, with the proportion of Caucasian patients as the covariate. Subgroup analysis was performed by specific IL-17 inhibitors. Results: Of the 1569 potentially relevant studies, sixteen RCTs were included. For PASI 75 response at week 12, the pooled logRR of the Asian group and Caucasian was 2.81 (95% Cl: 2.27–3.35, P<0.001) and 2.93 (95% Cl: 2.71 to 3.16, P<0.001), indicating no significant difference of efficacy between Asians and Caucasians. The meta regression did not show association of the proportion of Caucasians with the effect size either (β=0.3203, P=0.334). In subgroup analysis, the comparation results of secukinumab was consistent of the main analysis. Limitations: Only the short-term efficacy was explored. The data from Asian countries limited. Conclusions: The short-term efficacy of IL-17 inhibitors in the treatment of psoriasis has no significant difference between Caucasians and Asians.